2021
DOI: 10.3390/jpm12010016
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at Obesity Paradox in Acute Ischemic Stroke: Association Rule Mining

Abstract: Though obesity is generally associated with the development of cardiovascular disease (CVD) risk factors, previous reports have also reported that obesity has a beneficial effect on CVD outcomes. We aimed to verify the existing obesity paradox through binary logistic regression (BLR) and clarify the paradox via association rule mining (ARM). Patients with acute ischemic stroke (AIS) were assessed for their 3-month functional outcome using the modified Rankin Scale (mRS) score. Predictors for poor outcome (mRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…In addition, obesity increases the risk of hypertension, diabetes and dyslipidemia, which are non-modifiable risk factors for stroke. [15] In this study, 41 samples with a Well's score of 1 and a moderate probability of DVT (97.6%) had no complaints of DVT and were therefore classified as asymptomatic DVT. Another study reported that symptomatic DVT occurred in 19% of the sample, or 8 of 42 patients with DVT.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, obesity increases the risk of hypertension, diabetes and dyslipidemia, which are non-modifiable risk factors for stroke. [15] In this study, 41 samples with a Well's score of 1 and a moderate probability of DVT (97.6%) had no complaints of DVT and were therefore classified as asymptomatic DVT. Another study reported that symptomatic DVT occurred in 19% of the sample, or 8 of 42 patients with DVT.…”
Section: Discussionmentioning
confidence: 87%
“…After reviewing previous studies, primary association rules that satisfied “minimum support >0.01” and “minimum reliability >0.1” were extracted while considering the study’s characteristics [ 22 ]. Coincidences or unrelated patterns (lift ≤ 1) were excluded [ 23 ]. The extracted final pattern was visualized as a network graph using the arulesViz library of R [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are 20 studies which deals with application of Arti cial Intelligence and machine learning models in modalities like detection, outcome prediction and risk prediction associated with Acute Ischemic Stroke [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], Table 3.…”
Section: Acute Ischemic Strokementioning
confidence: 99%
“…Kai Wang et al explored the predictors of death in acute ischemic stroke (AIS) patients within 1 year based on machine learning (ML) algorithms and found that clinicians may use the network calculator established in this study, which is based on the XGB model, to assist them make more individualized and logical treatment decisions [20]. Pum-Jun Kim et al performed a binary logistic regression (BLR) and association rule mining (ARM) to analyze the data and investigate the relationship between obesity and stroke outcomes found that at three months, the outcomes of patients with acute ischemic stroke (AIS) are improved by obesity [25]. Obesity had a favorable effect on the result, according to the binary logistic regression (BLR) study.…”
Section: Risk Predictionmentioning
confidence: 99%